The prevalence of unhealthy alcohol and drug use among inpatients in a general hospital. Issue 3 (2nd July 2020) - Wakeman, Sarah E.; Herman, Grace; Wilens, Timothy E.; Regan, Susan
Abstract: Background: Unhealthy substance use is a growing public health issue. Intersections with the health care system offer an opportunity for intervention; however, recent estimates of prevalence for unhealthy substance use among all types of hospital inpatients are unknown. Methods: Universal screening for unhealthy alcohol or drug use was implemented across a 999-bed general hospital between January 1 and December 31, 2015. Nurses completed alcohol screening using the Alcohol Use Disorders Identification Test alcohol consumption questions (AUDIT-C) with a cutoff of ≥5 for moderate risk and ≥8 for high risk and drug screening using the single-item screening question with ≥1 episode of use considered positive. Results: Out of 35, 288 unique inpatients, screens were completed on 21, 519. There were 3, 451 positive screens (16% of all completed screens), including 1, 291 (6%) moderate risk and 1, 111 (5%) high risk screens for alcohol and 1, 657 (8%) positive screens for drug use. Among screens that were positive for moderate- or high-risk alcohol use, 221 (17%) and 297 (27%), respectively, were concurrently positive for drug use. The majority (61%) of patients with unhealthy alcohol use was on the medical services. Men, those who were white or Hispanic, middle-aged, single, unemployed, or screened positive for drug use were more likely to screen positive for high-risk alcohol use. Those who were younger, single, worked less than full time, or screened high risk for alcohol were more likely to screen positive for drug use. Discordance between diagnosis coding and screening results was noted: 29% of high-risk alcohol use screens had no alcohol diagnosis coding associated with that admission, and 51% of patients with a DSM-IV ( Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition ) diagnosis code of alcohol dependence had AUDIT-C scores of <8. Conclusions: Across a general hospital, 16% of patients screened positive for unhealthy substance use, with the highest volume on medical floors. Nursing-led screening may offer an opportunity to identify and engage patients with unhealthy substance use during hospitalization.